Prolonged cognitive–motor impairments in children and adolescents with a history of concussion. (12th May 2016) - Dalecki, Marc; Albines, David; Macpherson, Alison; Sergio, Lauren E
Aim: We investigated whether children and adolescents with concussion history show cognitive–motor integration (CMI) deficits.Method: Asymptomatic children and adolescents with concussion history (n = 50; mean 12.84 years) and no history (n = 49; mean: 11.63 years) slid a cursor to targets using their finger on a dual-touch-screen laptop; target location and motor action were not aligned in the CMI task.Results: Children and adolescents with concussion history showed prolonged CMI deficits, in that their performance did not match that of no history controls until nearly 2 years postevent.Conclusion: These CMI deficits may be due to disruptions in fronto-parietal networks, contributing to an increased vulnerability to further injury. Current return-to-play assessments that do not test CMI may not fully capture functional abilities postconcussion.